CAUSES OF HEPATOMEGALY IN 60 CASES SUDANESE PATIENTS, GEZIRA CENTRAL SUDAN - Mohammed, Moawia Elbalal; Saeed, Osman Khalfalla; A. Mohamadani, Ahmed (مجلة الجزيرة للعلوم الصحية; مجلد 6 عدد 1 (2010), 2010)
Chronic liver disease like: Hepatitis, schistosomiasis and hepatocellular carcinoma (HCC) are common in Sudan. The objective of this descriptive prospective clinicopathological, study is to determine the common symptoms and causes of hepatomegaly, excluding periportal fibrosis due to schistosomiasis as it is a very common cause of hepatomegaly in this area of Sudan.  Sixty cases presenting with hepatomegaly to Wadmedani Teaching Hospital were included in this study during the period form March 1996 to September 1997. A protocol including a detailed history, physical examination, blood work up, ultrasonography and liver biopsies, was followed. Thirty five were males and 25 were females. Twenty cases (33.3%) had primary hepatocellular carcinoma (HCC) with a males to female ratio of 7:3. Chronic Active Hepatitis (CAH) was found in 6 cases (10%), while active cirrhosis, metastasis and tinny insufficient specimens accounted for 4 cases (6.6%) each. Chronic Persistent Hepatitis (CPH) and a normal histology were seen in 3 cases for each (5%).This study concludes that HCC was the most frequent cause of hepatomegaly in studied group .